Relationship between maternal vitamin D status in the first trimester of pregnancy and maternal and neonatal outcomes: a retrospective single center study - Meng Ni; Qianqian Zhang; Jiuru Zhao; Qianwen Shen; Dongting Yao; Tao Wang; Zhiwei Liu (BMC Pediatrics, 2021)
Abstract Background This study aimed to investigate the relationship between maternal serum vitamin D status in the first trimester of pregnancy and maternal as well as neonatal outcomes, considered the prevalence of vitamin D deficiency (serum 25(OH)D < 50 nmol/L) around the world, especially in the pregnant women. Methods From January 2015 to December 2016, in this cross-sectional retrospective study, we enrolled women receiving regular prenatal examinations and giving birth in the International Peace Maternity and Child Health Hospital. Cases confirmed as multiple pregnancy, incomplete medical records, and vitamin D level recorded after 13 weeks of gestation were excluded. A total of 23,394 mother-infant pairs were included ultimately. Obstetric and neonatal information were extracted from the database. Maternal serum vitamin D concentration was measured by chemiluminescence microparticle immunoassay. Logistic regression analysis (unadjusted and adjusted models) was used to analyze the association between vitamin D and maternal and neonatal outcomes. Results The average 25(OH) D concentration was 43.20 ± 0.10 nmol/L; 67.09% of patients were vitamin D deficient(25(OH) D < 50.00 nmol/L), 29.84% were vitamin D insufficient (50 nmol/L ≤ 25(OH)D < 75 nmol/L), 3.07% were sufficient (25(OH)D ≥ 75 nmol/L). The maternal 25(OH)D levels varied with age, pre-pregnancy BMI, season when blood sample was collected, number of previous-pregnancy. Notably, newborns delivered by women with deficient vitamin D status had a higher incidence rate of admission to NICU (Deficiency: 12.20% vs Insufficiency: 10.90% vs Sufficiency: 11.70%, P bonferroni = .002) and a longer stay (deficiency: 6.2 ± 4.1 days vs insufficiency: 5.9 ± 3.1 days vs sufficiency: 5.1 ± 2.1 days, P bonferroni = .010). Moreover, maternal vitamin D deficiency was a dependent risk factor for admission to NICU (unadjusted OR = 1.35, 95% CI,1.05–1.74 P bonferroni = .022; adjusted OR = 1.31, 95% CI,1.010–1.687 P bonferroni = .042). Conclusions Maternal vitamin D deficiency (25(OH) D < 50 nmol/L) was prevalent in eastern coastal China. The incidence rate of GDM as well as preeclampsia was higher in vitamin D insufficient group while vitamin D deficiency group was liable to intrauterine infection when compared with the other two groups. Most importantly, low vitamin D status in the first trimester of pregnancy was a dependent risk factor for admission to NICU. More well-designed perspective researches are necessary to clarify the role of vitamin D in the early stage of pregnancy.